To change or not to change - that is the question: a qualitative study of lifestyle changes following acute myocardial infarction - Nicolai, Jennifer; Müller, Nicole; Nöst, Stefan; Wilke, Stefanie; Schultz, Jobst-Hendrik; Gleißner, Christian A.; Eich, Wolfgang; Bieber, Christiane (Chronic illness, 2018)
The purpose of this study was to investigate key factors related to lifestyle changes following acute myocardial infarction (AMI) by eliciting survivors' subjective needs for, attitudes towards and experiences with behaviour changes in their everyday life to improve future interventions promoting lifestyle changes.